Performance evaluation of image segmentation algorithms on microscopic image data - Beneš, Miroslav; Zitová, Barbara (Journal of microscopy, 2015)
In our paper, we present a performance evaluation of image segmentation algorithms on microscopic image data. In spite of the existence of many algorithms for image data partitioning, there is no universal and 'the best' method yet. Moreover, images of microscopic samples can be of various character and quality which can negatively influence the performance of image segmentation algorithms. Thus, the issue of selecting suitable method for a given set of image data is of big interest. We carried out a large number of experiments with a variety of segmentation methods to evaluate the behaviour of individual approaches on the testing set of microscopic images (cross-section images taken in three different modalities from the field of art restoration). The segmentation results were assessed by several indices used for measuring the output quality of image segmentation algorithms. In the end, the benefit of segmentation combination approach is studied and applicability of achieved results on another representatives of microscopic data category - biological samples - is shown.
Keywords: Microscopy; algoritmy; myši; mikroskopie; Mice; počítačové zpracování obrazu; zvířata; Animals; Algorithms; Image Processing, Computer-Assisted